Phylogenetic and Systematic Value of Leaf Epidermal Characteristics in Some Members of Nigerian Fabaceae - Alege, Gbenga Olorunshola; Shaibu, Daniel Ojima (International Journal of Applied Sciences and Biotechnology, 2015)
This study was undertaken at the Botanical Garden of Biological Sciences Department, Kogi State University, Anyigba with the aim of assessing the systematic and phylogenetic relevance of leaf epidermal attributes in the 10 selected species of Fabaceae. Stomata, trichomes and epidermal cell attributes were taken from adaxial and abaxial leaf surfaces. Results obtained in this study revealed that all the 10 plant species considered possess hypo-amphistomatic leaf condition, paracytic stomata type, polygon and irregular shape epidermal cells(on the abaxial surface) which points to their common ancestry. All the analyzed leaf epidermal traits considered on the adaxial and abaxial surfaces showed significant variations among the 10 studied plant species which indicates that genetic diversity exists among members of Fabaceae for their delimitation. It was also observed that all the plants with tree habit considered in this study (i.e Delonix regia, Parkia biglobosa, Senna siamea, Daniella oliveri and Caesalpinia pulcherrima) lack stomata on the adaxial surfaces which strongly suggest that absence of stomata on the adaxial surface may be peculiar to Legumes with such habit. Cluster analysis revealed 2 major clusters and 2 sub-clusters with the first cluster comprising only Senna siamea and Caesalpinia pulcherrima which confirms their close phylogenetic relationship. Variations in trichomes, stomata and epidermal attributes were obvious and could be used to resolve systematic and phylogenetic problems in this family. Int J Appl Sci Biotechnol, Vol 3(2): 301-307 DOI: http://dx.doi.org/10.3126/ijasbt.v3i2.12733